Sexual Dysfunction in the 'Eden of Love': Psychosocial Responses to Impotence in British First World War Veterans. (31st October 2019) - Johnson, Bethan
Abstract: Contemporary estimates and more recent research into the correlation between military service and sexuality suggest that, among the millions of men returning to Great Britain following combat in the First World War, more than half a million had sustained physical or psychological injuries that would have rendered them sexually impotent. Many studies have addressed war disabilities, unstable masculinities, and changing sexual mores in the British interwar period; however, the impotent Great War veteran, the embodiment of all three of these phenomena, has remained on the fringes of historical analysis. This article recovers the subjective experiences of Great War veterans who were made impotent as a result of their combat service, using the written records many left behind. These testimonials reveal a strong negative affectivity and sense of isolation in impotent veterans due to their condition, despite its prevalence. The article uses works from popular science, literature, and film to demonstrate how the convergence of historic prejudice against impotent men and mounting pressures placed on sexual performance and the ability to reproduce induced this internal turmoil, an anxiety unique to impotent combat veterans. By exploring impotent veterans' attempts to reconcile themselves to their condition, this article provides insights into the instability of masculinity, diversifies historical articulations of wartime disabilities, and complicates narratives about revolutionary sexual change in interwar British society.